2021
DOI: 10.1177/17588359211008399
|View full text |Cite|
|
Sign up to set email alerts
|

Cell therapies in ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is the most important cause of gynecological cancer-related mortality. Despite improvements in medical therapies, particularly with the incorporation of drugs targeting homologous recombination deficiency, EOC survival rates remain low. Adoptive cell therapy (ACT) is a personalized form of immunotherapy in which autologous lymphocytes are expanded, manipulated ex vivo, and re-infused into patients to mediate cancer rejection. This highly promising novel approach with curative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…TIL therapy offers an important new therapeutic approach to patients with HGSOC, although, to date, response rates equivalent to those demonstrated in metastatic melanoma using established TIL manufacture techniques have not been achieved in ovarian cancer (Sarivalasis et al, 2021, Pedersen et al, 2018. A contemporary clinical trial of TIL therapy in ovarian cancer has demonstrated limited e cacy compared to metastatic melanoma trials, with all patients achieving a best response of stable disease and a progression free survival between 3-5 months (Pedersen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TIL therapy offers an important new therapeutic approach to patients with HGSOC, although, to date, response rates equivalent to those demonstrated in metastatic melanoma using established TIL manufacture techniques have not been achieved in ovarian cancer (Sarivalasis et al, 2021, Pedersen et al, 2018. A contemporary clinical trial of TIL therapy in ovarian cancer has demonstrated limited e cacy compared to metastatic melanoma trials, with all patients achieving a best response of stable disease and a progression free survival between 3-5 months (Pedersen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that CDC42EP3 had the most relevance with several TILs, including NK cell, Tcm_CD4 and Tgd. NK-based immunotherapy strategy, especially cytokine-induced killer (CIK) cells, has been extensively studied for decades ( Sarivalasis et al, 2021 ). The clinical efficacy of CIK cells was evaluated in patients with advanced epithelial ovarian cancer in a phase 3 clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…While the therapy was safe and only resulted in grade 1 or 2 toxicities, no reduction in tumor burden was observed in any of the six tested patients [ 25 ]. This and several other clinical trials in OC targeting different antigens have demonstrated the poor success of CAR T-cell therapies in OC, much like in several other solid tumors [ 24 , 26 ]. TCR T-cell therapy in OC on the other hand is still in its early phase with 19 Phase I/II clinical trials registered in (accessed on 15 August 2022).…”
Section: Immunotherapies In Ocmentioning
confidence: 97%
“…On the other hand, CAR T-cell therapy uses antigen-binding regions of antibodies that are fused to intracellular T-cell signaling domains, thereby allowing them to recognize surface antigens independent of HLA presentation. However, while CAR T cells can only elicit an immune response to surface antigens, TCR T cells can recognize antigens from any subcellular compartment [ 24 ]. 32 Phase I/II clinical trials of CAR T-cell therapies have been registered in (accessed on 15 August 2022) directed towards several antigens including B7-H3, TAG72, ALPP, CD133, C-met, FRα, FRβ, HER2, mesothelin, and MUC-1.…”
Section: Immunotherapies In Ocmentioning
confidence: 99%